Kekuatan Bending Rangka H-Beam Komposit Sandwich Menggunakan Core Polimer Produk 3D Printing dan Skin Serat Karbon - Ridlwan Muhammad; Pradana M. D. N (Jurnal Inovasi Teknologi Terapan, 2026)
Additive manufacturing (AM) has emerged as an effective fabrication approach for producing lightweight structural components with high geometric flexibility; however, its relatively limited mechanical performance restricts its direct application in load-bearing structures. In contrast, carbon fiber-reinforced composite structures offer superior stiffness-to-weight and strength-to-weight characteristics, but conventional composite manufacturing processes are often labor-intensive, time-consuming, and less adaptable to complex structural profiles. To address these limitations, this study proposes an integrated fabrication strategy for composite H-beam structures that combines the design flexibility of fused deposition modeling (FDM) with the mechanical efficiency of carbon fiber reinforcement. The proposed method utilizes FDM to fabricate H-beam cores using PLA+ and ABS materials, which are subsequently reinforced with carbon twill fabric and carbon prepreg layers through a vacuum bagging process. A controlled curing process is conducted at 70 °C for 240 min to improve composite consolidation and achieve optimal mechanical performance. The effects of material selection and reinforcement configuration are evaluated through bending tests to assess structural strength and rigidity. The results demonstrate that integrating 3D printing with vacuum-assisted composite fabrication enables the production of lightweight H-beam structures with enhanced mechanical performance and improved manufacturing flexibility compared with conventional approaches.